Long-Term Retarded Release for the Proteasome Inhibitor Bortezomib through Temperature-Sensitive Dendritic Glycopolymers as Drug Delivery System from Calcium Phosphate Bone Cement - Lai, Thu Hang; Keperscha, Bettina; Qiu, Xianping; Voit, Brigitte; Appelhans, Dietmar (Macromolecular Rapid Communications, 2021)
For the local treatment of bone defects, highly adaptable macromolecular architectures are still required as drug delivery system (DDS) in solid bone substitute materials. Novel DDS fabricated by host–guest interactions between β-cyclodextrin-modified dendritic glycopolymers and adamantane-modified temperature-sensitive polymers for the proteasome inhibitor bortezomib (BZM) is presented. These DDS induce a short- and long-term (up to two weeks) retarded release of BZM from calcium phosphate bone cement (CPC) in comparison to a burst release of the drug alone. Different release parameters of BZM/DDS/CPC are evaluated in phosphate buffer at 37 °C to further improve the long-term retarded release of BZM. This is achieved by increasing the amount of drug (50–100 µg) and/or DDS (100–400 µg) versus CPC (1 g), by adapting the complexes better to the porous bone cement environment, and by applying molar ratios of excess BZM toward DDS with 1:10, 1:25, and 1:100. The temperature-sensitive polymer shells of BZM/DDS complexes in CPC, which allow drug loading at room temperature but are collapsed at body temperature, support the retarding long-term release of BZM from DDS/CPC. Thus, the concept of temperature-sensitive DDS for BZM/DDS complexes in CPC works and matches key points for a local therapy of osteolytic bone lesions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: calcium phosphate cements; dendritic glycopolymers; drug delivery systems; proteasome inhibitors; temperature-sensitive polymers